Life and Death in the Body of Christ - Studt, S.J., Eric (Lumen et Vita, 2017)
Focusing on 1 Corinthians, I argue for a literal reading of Paul’s understanding of life and death in the body of Christ. Recent research carried out by Dale Martin and Troels Engberg-Pedersen has uncovered a Stoic notion of pneuma in Paul’s writings. That is to say, Paul understood pneuma as a material substance that allows for life, perception, and knowledge. Paul believed that human beings are born with a fleshly pneuma, but God’s pneuma is given at baptism. Those possessing God’s pneuma literally see a different reality and are materially bound to other believers. Since for Paul the risen Christ is a pneumatic body, believers are also materially bound to Christ to form a single pneumatic body, the body of Christ. The body of Christ is not a metaphor, but an actual material body that is made up of God’s pneuma. Ultimately, to have a share in God’s pneuma means eternal life with the risen Christ and existence apart from God’s pneuma means death. This paper treats 1 Cor. 11:17-34 as a case study. In this pericope Paul warns that the body of the Lord acts as a poison, causing sickness and death, to those who participate unworthily in the Lord’s supper. “Unworthiness” here refers to the factionalism that was plaguing the Corinthian community. Paul believed that the Corinthians were literally killing the body of Christ—as well themselves individually—by tearing apart the corporate pneumatic body of believers through factionalism. In short, for Paul factionalism means death.